An in silico assessment on the potential of using saline infusion to overcome non-confluent coagulation zone during two-probe, no-touch bipolar radiofrequency ablation of liver cancer. (February 2023) - Yip, Wai P.; Kho, Antony S.K.; Ooi, Ean H.; Ooi, Ean T.
Abstract: No-touch bipolar radiofrequency ablation (bRFA) is known to produce incomplete tumour ablation with a 'butterfly-shaped' coagulation zone when the interelectrode distance exceeds a certain threshold. Although non-confluent coagulation zone can be avoided by not implementing the no-touch mode, doing so exposes the patient to the risk of tumour track seeding. The present study investigates if prior infusion of saline into the tissue can overcome the issues of non-confluent or butterfly-shaped coagulation. A computational modelling approach based on the finite element method was carried out. A two-compartment model comprising the tumour that is surrounded by healthy liver tissue was developed. Three cases were considered; i) saline infusion into the tumour centre; ii) one-sided saline infusion outside the tumour; and iii) two-sided saline infusion outside the tumour. For each case, three different saline volumes were considered, i.e. 6, 14 and 22 ml. Saline concentration was set to 15% w/v. Numerical results showed that saline infusion into the tumour centre can overcome the butterfly-shaped coagulation only if the infusion volume is sufficient. On the other hand, one-sided infusion outside the tumour did not overcome this. Two-sided infusion outside the tumour produced confluent coagulation zone with the largest volume. Results obtained from the present study suggest that saline infusion, when carried out correctly, can be used to effectively eradicate liver cancer. This presents a practical solution to address non-confluent coagulation zone typical of that during two-probe bRFA treatment. Graphical abstract: Highlights: Saline infusion to overcome non-confluent heating during bRFA was examined. Infusion at tumour centre prevents non-confluency if saline volume is ≥ 14 ml. One-sided infusion outside the tumour cannot prevent non-confluent heating. Two-sided infusion overcomes non-confluent heating with sufficient ablation margin.